3x-2y+0 X+2y=-5 I'm confused. Its like the other one I posted.
3x - 2y = 0 3x = 2y y = 1.5 x Place in eqtn 2 x + 3 x = -5 4x = -5 x = -5/4 But that is using substitution if that the answer LOLZ :D
Multiply equation 2 by 3 to get 3x + 6y = -15, then take this away from eqequation 1. The x's are eliminated, so solve for y.
Randi Candi, you're real smart. Thanksalot for helping me on this problem.
you are VERY welcome :D :D Thank You XD XD
Join our real-time social learning platform and learn together with your friends!